2016
DOI: 10.1016/j.ijggc.2015.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Impact of wettability alteration on 3D nonwetting phase trapping and transport

Abstract: We investigate capillary trapping and fluid migration via x-ray computed microtomography (xray CMT) of nonwetting phase (air) and wetting phase (brine) in Bentheimer sandstone cores which have been treated to exhibit different degrees of uniform wettability. X-ray CMT scans were acquired at multiple steps during drainage and imbibition processes, as well as at the endpoints; allowing for assessment of the impact of wettability on nonwetting phase saturation and cluster size distribution, connectivity, topology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 51 publications
(84 reference statements)
2
37
0
Order By: Relevance
“…In 2008, Kumar proposed a well‐controlled method to generate a mixed‐wet core in a reservoir core material. The procedure is first to saturate the strongly water‐wet core and then rapidly freeze the core followed by flushing with organic chemical ‐ Octadecyltrichlorosilane (OTS) to render the exposed pore surface hydrophobic (Herring et al,). The core is then thawed, drained and dried.…”
Section: Methodsmentioning
confidence: 99%
“…In 2008, Kumar proposed a well‐controlled method to generate a mixed‐wet core in a reservoir core material. The procedure is first to saturate the strongly water‐wet core and then rapidly freeze the core followed by flushing with organic chemical ‐ Octadecyltrichlorosilane (OTS) to render the exposed pore surface hydrophobic (Herring et al,). The core is then thawed, drained and dried.…”
Section: Methodsmentioning
confidence: 99%
“…Their work also indicated that even though the two‐pore network model (pore doublet model) [ Chatzis and Dullien , ] can well describe snap‐off mechanism, it fails in describing the bypass trapping when considering the fluid distribution. Later, the effects of Ca [ Chatzis et al ., ; Soroush et al ., ; Kimbrel et al ., ] and pore structure [ Tanino and Blunt , ; Chaudhary et al ., ; Geistlinger et al ., ] on immiscible flow and capillary trapping were extensively investigated using advanced visualization technology, including X‐ray computed tomography core‐flooding experiments [ Krevor et al ., ; Pentland et al ., ; El‐Maghraby and Blunt , ; Iglauer et al ., ; Andrew et al ., ; Geistlinger et al ., ; Xu et al ., ; Zuo and Benson , ; Li et al ., ; Niu et al ., ; Khishvand et al ., ; Rahman et al ., ; Herring et al ., , ], and micromodel experiments [ Zhang et al ., , ; Wang et al ., ; Kazemifar et al ., ; Cao et al ., ; Chang et al ., , ; Zhao et al ., ]. These studies indicated that (1) at Ca on the order of 10 −7 or even smaller, the snap‐off trapping mechanism by the precursor‐thin film dominates, and it is enhanced by the roughness of pore surface and the throat‐body aspect ratio of pores; (2) at Ca > 10 −7 , the main trapping mechanism involves propagation of invading fluid fingers that lead to islands of defending fluid being bypassed.…”
Section: Introductionmentioning
confidence: 99%
“…When wettability is involved, the capillary trapping mechanism is more complicated, and conflicting results have been reported. In many studies, the trapped defending fluid saturations decreased as the medium becomes less water‐wetting [ Herring et al ., ], or more CO 2 /oil‐wetting [ Morrow , ; Iglauer et al ., ; Chaudhary et al ., ; Rahman et al ., ]. Herring et al .…”
Section: Introductionmentioning
confidence: 99%
“…The multiphase interactions combining several factors (including intrinsic topological features, gravity, capillary, and wettability) determine macroscopic drainage properties, such as the residual saturation of wetting phase and the temporal/spatial distributions of saturated zones (Yang et al, 1988;Herring et al, 2016;Li et al, 2017). The majority of previous experiments and numerical models of drainage and injection are focusing on the macroscopic parameters, e.g., porosity, permeability, system size and aspect ratio (Succi et al, 1989;Toussaint et al, 2005;Babadagli et al, 2015;Moura et al, 2015;Rognmo et al, 2017;March et al, 2018), in which the spatial configuration, pore connectivity and their influences on liquid retention are ignored (Prat, 1995;Lin et al, 2018;Yekta et al, 2018).…”
Section: Introductionmentioning
confidence: 99%